Magnetic fluid sealing status estimation based on acoustic emission monitoring - Chen, Nuo; Li, Decai; Xue, Jinyu; Yin, Yuan; Li, Yanwen (Frontiers in Materials, 2022)
The aim of the study was to analyze acoustic emission (AE) signals generated in different magnetic fluid sealing processes to estimate the status of the seal. Based on a magnetic fluid rotary sealing experimental setup, the AE sensor is respectively attached to the shell at the corresponding position of the seal, and the external pressure is applied to the magnetic fluid seal by a gas supply system. As the pressure gradually increases, the magnetic fluid sealing rings under different pole teeth are gradually broken, and processes such as pressure transfer between the seal stages occur. These processes generate different AE signals, which are collected by the sensors. The results show that the root-mean-square values of AE signals generated at the moment of sealing failure are different from those generated before and after. At the same time, by analyzing the characteristic values of AE signals generated in the whole process, we can infer the time when the rupture begins under different pole pieces and further estimate the status of the magnetic fluid seal. For the first time, this research demonstrates the experimental and data analysis procedures of AE technology for magnetic fluid seals.